Sapientia Salomonis (Weisheit Salomos) - Niebuhr, Karl-Wilhelm; Ameling, Walter; Blischke, Mareike Verena; Blischke, Folker; Fürst, Alfons; Hirsch-Luipold, Rainer; Nesselrath, Heinz-Günther; Niehoff, Maren R.; Reiterer, Friedrich V. (SAPERE, 2015)
This volume contains the Greek text with facing German translation of the Sapientia Salomonis, along with a detailed introduction and essays on the interpretation and cultural background of the work